Monthly unannounced pill counts for monitoring HIV treatment adherence: tests for self-monitoring and reactivity effects. - Kalichman, Seth C; Amaral, Christina; Swetsze, Connie; Eaton, Lisa; Kalichman, Moira O; Cherry, Chauncey; Detorio, Mervi; Caliendo, Angela M; Schinazi, Raymond F (HIV clinical trials, 2010)
Unannounced home-based pill counts conducted in person or on the telephone are reliable and valid for monitoring medication adherence. However, expecting to have one's pills counted, organizing medications for pill counts, and increased attention from the person conducting the pill counts may have reactive effects and inadvertently improve adherence. The current study determined whether monthly unannounced pill counts conducted by telephone influence adherence over time.
Keywords: Adult; Aged; Anti-Retroviral Agents; Cohort Studies; Female; Health Behavior; HIV Infections; Humans; Male; Medication Adherence; Middle Aged; Self Medication; Social Support; Telephone; Viral Load; Young Adult